Detection and Enumeration of Listeria spp. and Listeria monocytogenes in fruit juices - Chai, Sze Fan (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Listeria spp. is an important foodbome bacterial group that is able to cause food poisoning outbreak and diseases among human. In this research, five types of fruit juices were sampled to enumerate and detect the presence of Listeria spp. and Listeria monocytogenes (L. monocytogenes). The Most Probable Number (MPN) method was used for enumeration and specific Polymerase Chain Reaction (PCR) was performed targeting the virulence gene, hlyA gene with expected size of 730 bp to determine the presence of L. monocytogenes in the fruit juice samples. The hlyA gene confers haemolytic properties in L. monocytogenes as it produces Listeriolysin 0 (LLO) which involves actively in cell lysis process of phagocytic membrane. Out of the 50 fruit juice samples, all were negative for the presence of the hlyA gene. MPN analysis showed that the results of all samples showed estimated microbial load of Listeria species as more than 1100 MPN/g. For standard plate count, only three apple juice samples out of 10 apple juice samples showed range from 2.8x 104 to 1.9x 108 CFUlml and only one honeydew juice sample out of 10 honeydew juice samples showed 4.0x 103 CFU/ml. Factors contributing to the absence of L. monocytogenes in the fruit juice samples were proper hygienic and sanitary production and processing practices applied by the workers in the fruit stalls and restaurants. Besides, low chances to get cross-contamination during fruit juices preparation and proper water supplies used in sampling sites also led to the absent of L. monocytogenes in fruit juice samples.